China's Global Investment and Maritime Flows in the Context of the Belt and Road Initiative. Issue 129 (4th May 2021) - Hu, Zhi-Hua; Liu, Chan-Juan; Lee, Paul Tae-Woo
ABSTRACT: This article aims to investigate mutual impacts between China's global investment and maritime transportation system as a primary means for trading since the Belt and Road Initiative (BRI) has been launched. This study collected China's global investment data categorized by independent economy entities with featured data, including investment capital, industrial field, and the maritime flows generated from the previous study. The country-level mutual relations in the context of the BRI are formulated and investigated by data-driven geographical visualization methods. The test results reveal both the degree and tendency of China's initiative impacting the global investment and the possible patterns and inertial power of investment on a globally regional initiative, primarily focusing on the concerns and contributions of the maritime transportation system in promoting investment and the BRI.